Identification of the pollinizer for a new almond genotype ‘Karaj 33’ - Abdel-Reza Jamshidi (University of Birjand, 2021)
Purpose: Most almond cultivars grown in Iran exhibit gametophytic self-incompatibility. Therefore, they need to be pollinated by cross-compatible cultivars that bloom in the same time to produce commercial crop. One of the new almond genotypes is Karaj 33, which has very late flowering, high productivity, paper shell, high percentage of kernel to fruit, no double and twin kernel, and self-incompatible.Research method: In order to select the suitable pollinizer for ‘Karaj 33’, an experiment was conducted using fruit set under field conditions and fluorescence microscopy methods, in which Tuono, Shekofeh and H were evaluated as pollen donors. Findings: All almond cultivars/genotypes had high (80-85%) pollen germination. Tuono and H bloomed earlier (from 24th to 29th March), whereas Shekofeh and then Karaj 33 bloomed later (from 26th March to 1st April and 30th March to 3rd April, respectively). Cross-compatibility was confirmed in all the three cultivars/genotype by both methods. Shekofeh had almost overlapping flowering time with Karaj 33. The penetration rate of Shekofeh pollen tube was faster so that 96 h after cross-pollination, it reached the base of Karaj 33 style, while the other two reached 120 h later. The highest final fruit set was observed with the cross of Karaj 33 × Shekofeh. Research limitations: No limitations were found. Originality/Value: we can consider Shekofeh as a suitable pollinizer for Karaj 33.